A Bumpy Ride of Mycobacterial Phagosome Maturation: Roleplay of Coronin1 Through Cofilin1 and cAMP - Saha, Saradindu; Hazra, Arnab; Ghatak, Debika; Singh, Ajay Vir; Roy, Sadhana; BoseDasgupta, Somdeb (Frontiers in Immunology, 2021)
Phagosome-lysosome fusion in innate immune cells like macrophages and neutrophils marshal an essential role in eliminating intracellular microorganisms. Generally, in microbe-challenged macrophages, phagosome-lysosome fusion occurs four to six hours post phagocytic uptake of the microbe. However, live pathogenic mycobacteria can retard its lysosomal delivery up to twenty hours post phagocytic uptake wherein it mitigates the macrophage stress and upregulates proteins for acid tolerance inside lysosomes. The exact sequence of events through which, mycobacteria retards phagolysosome formation remains an enigma. The macrophage coat protein Coronin 1, is recruited and retained by mycobacteria on the phagosome membrane to retard its maturation by hindering the access of phagosome maturation factors. Mycobacteria infected macrophages exhibit an increased level of cAMP and based on receptor stimulus Coronin 1 expressing cells exhibit a higher level of cAMP than non-Coronin 1 expressing cells. Here we have shown that infection of bone marrow-derived macrophages with H37Rv causes a Coronin 1 dependent rise of intracellular cAMP levels at the vicinity of the phagosomes. This increased cAMP fuels cytoskeletal protein Cofilin 1 to depolymerize F actin into G actin at the vicinity of the mycobacteria containing phagosome. Owing to reduced F actin levels the movement of the phagosome towards the lysosomes is hindered, thus contributing to the retarded phagosome maturation process. Additionally, Coronin 1 mediated up-regulation of Cofilin also contributes towards the prevention of phagosomal acidification, which further aids in the retardation of phagosome maturation. Taken together our study provides firsthand information on Coronin1 mediated retardation of phagosome maturation which therefore can be utilized in developing novel peptidomimetics as part of host-directed therapeutics against tuberculosis.